Pan Cayman House - (:unkn) unknown (Dewitt industries Corp., Hollywood, Florida, 2009)
Description of the card is as follow: "Pan Cayman House - P.O. Box 440, Grand Cayman Island, British West Indies, 10 air-conditioned deluxe rental apartments, completely furnished, located on Famous Seven Mile Beach." Addressed to Mr. and Mrs. D.M. Stanley, Alliance, Ohio, U.S.A. Affixed to the postcard is an 8 cents Cayman Islands stamp.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Postcards; Cayman Islands; Hotels--Cayman Islands; Beaches--Cayman Islands; Vacation rentals--Cayman Islands; Rental housing--Cayman Islands; Vacation homes--Cayman Islands; [1970]